Dust in the wind: Renewable energy and the limits of South Africa’s developmental state - Borchardt, Stephanie Paula (New Agenda: SA Journal of Social and Economic Policy, 2025)
South Africa’s Renewable Energy Independent Power Producer Procurement Programme (REIPPPP) is widely celebrated for attracting private investment into renewable energy while embedding socio-economic development goals. Positioned as a flagship initiative of the country’s green developmental state, the programme promises inclusive growth through job creation, skills development, and community ownership. Yet this article critically examines the disjuncture between the programme’s technocratic design and its uneven implementation in remote host towns. Drawing on ethnographic fieldwork and a 2024 household survey in Sutherland, Northern Cape, it explores how the REIPPPP’s scorecard-driven framework struggles to engage with the layered social, institutional, and labour dynamics of marginalised rural towns in the Karoo. Despite substantial financial commitments to local development, implementation is undermined by skills shortages, substance abuse, fragmented governance, and limited community agency. These challenges expose the limits of South Africa’s developmental state, where technocratic procurement frameworks and rigid compliance metrics falter amid structural inequality and weak local capacity. By centring the construction phase and local experiences, the article argues that without more grounded, participatory, and justice oriented approaches, the REIPPPP risks reproducing the very exclusions it seeks to redress. The findings call for a reimagined energy transition, one that moves beyond metrics to engage meaningfully with the social realities shaping project outcomes in South Africa’s arid regions.